Carbon fibre waste recycling into hybrid nonwovens for electromagnetic interference shielding and sound absorption. (15th September 2021) - Pakdel, Esfandiar; Kashi, Sima; Baum, Thomas; Usman, Ken Aldren S.; Razal, Joselito M.; Varley, Russell; Wang, Xungai
Abstract: The increasing global use of carbon fibre (CF) in different industries has resulted in production of significant amounts of waste in the forms of CF-reinforced composites and dry CF scrap. The latter group which is mainly in the form of short fibres is generated during manufacturing of CF-reinforced composites and comprises a significant portion of total CF waste. However, little attention has been paid to recycling these waste fibres. This research provides a comprehensive understanding on the processability of CF waste into nonwovens using conventional textile machineries of carding and needle-punching, for applications in areas of electromagnetic interference (EMI) shielding and sound absorption. The carding of CF was carried out in the presence of polyamide 6 (PA6) fibres to minimise damages to CF during the recycling process. Hybrid CF/PA6 nonwovens were produced and the effects of operating parameters such as the number of carding passages, the ratio of CF/PA6 fibres (20/80, 50/50, and 80/20), and the number of cross-lapped web layers during the needle-punching process on the obtained features were explored. The results demonstrated that excellent EMI shielding effectiveness was achieved with the highest performance being 85 dB from the CF/PA6 80/20 samples. Increasing the content of CF, the number of carding passages and the thickness of nonwovens all positively contributed to enhancing the EMI shielding performance. The sound absorption performance of nonwovens was found to depend on the CF/PA6 ratio and the thickness of the tested samples. However, the second carding process negatively impacted on the sound absorption performance by reducing the fibres mass in final products. In addition, the relations between the composition of samples and employed methodologies with production yield, areal density, electrical conductivity and actual CF content of the developed nonwovens were all discussed. Graphical abstract: Image 1 Highlights: Hybrid nonwovens were produced using carbon (CF) waste and nylon (PA6) fibres. The CF/PA6 nonwovens provided an excellent EMI shielding effectiveness up to 85 dB. Increasing the content of CF, thickness of nonwovens and the number of cardings enhanced EMI shielding. The highest production yield of 87.4% was achieved for the CF/PA6 50/50 ratio. The developed nonwovens were promising for sound absorption applications.